Esophageal adenocarcinoma with white opaque substance observed by magnifying endoscopy with narrow band imaging. Issue 3 (28th August 2014) - Yoshii, Shunsuke; Kato, Motohiko; Honma, Keiichiro; Fujinaga, Tetsuji; Tsujii, Yoshiki; Maekawa, Akira; Inoue, Takuya; Hayashi, Yoshito; Akasaka, Tomofumi; Shinzaki, Shinichiro; Nishida, Tsutomu; Iijima, Hideki; et al.
<x xml:space="preserve">Abstract</x> White opaque substance (WOS) is observed in the gastric neoplasia of 0‐IIa type using magnifying endoscopy with narrow band imaging (NBI‐ME). Colonic and duodenal neoplasms with WOS have also been reported. Immunohistochemical examination with adipophilin reveals WOS in gastric neoplasms as lipid droplets, and WOS is specific for neoplasm with intestinal or gastrointestinal phenotype. We herein report a case of adenocarcinoma of the esophagogastric junction with WOS. A male patient in his sixties was found by esophagogastroduodenoscopy to have an esophageal elevated lesion. NBI‐ME showed whitish deposits that looked similar to WOS in gastric neoplasms. The patient underwent endoscopic submucosal dissection and the lesion was resected in a single piece. This tumor had diffuse positivity for adipophilin and gastrointestinal phenotype.